(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Combination therapy has more popularity and various merits over monotherapy (conventional dosage forms). Bilayer tablet technology is the best and most recent used example of combination dosage formulation. In the last decade, the single-dose formulation has the combination of two or three active pharmaceutical ingredients (API) increased in pharmaceutical industry. It is known for promoting patient convenience and compliance by reducing the number of dosages and enhancing the bioavailability of dosage forms. Bilayer or multilayer tablets are innovative forms of conventional oral drug delivery systems. Bilayer layer can be the only technology that has been used in different APIs for synergistic effect, to enhance the bioavailability or to avoid the interaction between the incompatible substance by separating them physically, and to enable the development of different drug release profiles (sustained release or controlled release, etc). The goal of this review is to give a general overview of the development and production of bilayer tablet technology and to highlight the issues encountered during the production of bilayer tablets as well as the expected solutions to these problems.